2016
DOI: 10.21829/myb.2016.2231457
|View full text |Cite
|
Sign up to set email alerts
|

Abundancia y distribución del género Pinus en Capulálpam de Méndez, Sierra Juárez, Oaxaca

Abstract: ResumenSe analizan los factores ambientales que determinan la abundancia y distribución de las diferentes especies comerciales y aprovechadas del género Pinus en el municipio de Capulálpam de Méndez, Oaxaca. Se utilizó la información de 636 sitios en áreas de aprovechamiento del inventario forestal del municipio llevado a cabo en 2013 para el Plan de Manejo 2015-2022, y 354 puntos adicionales de áreas con uso diferente al forestal. Se obtuvo información sobre la distribución espacial y análisis del nicho ecoló… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
2
1
0
6
Order By: Relevance
“…Of the lower elevation pine species found in this cluster, P. patula, P. teocote, and P. leiophylla are considered moderately sensitive to climate change, while P. douglasiana is considered tolerant (Gómez‐Mendoza and Arriaga 2007, Galicia et al 2015). Of these pines, P. patula had the broadest altitudinal range in our study, a pattern which was also seen in another study of Oaxacan pines (Ríos‐Altamirano et al 2016). P. patula is associated with more mesic sites in another studies (Rodríguez‐Trejo and Fulé 2003), and in our model was one of the few species to be significantly correlated with northern aspects, which are likely to be slightly more mesic compared to southern‐facing slopes at latitudes above the equator.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Of the lower elevation pine species found in this cluster, P. patula, P. teocote, and P. leiophylla are considered moderately sensitive to climate change, while P. douglasiana is considered tolerant (Gómez‐Mendoza and Arriaga 2007, Galicia et al 2015). Of these pines, P. patula had the broadest altitudinal range in our study, a pattern which was also seen in another study of Oaxacan pines (Ríos‐Altamirano et al 2016). P. patula is associated with more mesic sites in another studies (Rodríguez‐Trejo and Fulé 2003), and in our model was one of the few species to be significantly correlated with northern aspects, which are likely to be slightly more mesic compared to southern‐facing slopes at latitudes above the equator.…”
Section: Discussionsupporting
confidence: 89%
“…Despite the ecological and economic importance of pine and oak in Mexico, relatively little is known about the floristics of most species. We found that species composition was significantly correlated with altitude, topography, and soil characteristics (particularly soil nutrients and organic matter content), similar to results of other studies in Mexico where altitude is the most significant explanatory factor for Quercus (Meave et al 2006, Olvera-Vargas et al 2010 and Pinus species distributions (Yeaton 1982, Alba-L opez et al 2003, R ıos-Altamirano et al 2016. In general, altitude-related moisture availability is a well-established factor driving differentiation of pine and oak in montane regions around the globe-including in Costa Rica (Kappelle et al 1995), the Himalaya region in India (Chawla et al 2008, Singh et al 2009, Saha et al 2016, and in temperate United States (Abrams 1990, Kubiske and Abrams 1992, Ashton and Berlyn 1994, Fallon and Cavender-Bares 2018.…”
Section: Tree Species Distribution and Community Differentiationsupporting
confidence: 89%
See 1 more Smart Citation
“…El estudio se llevó a cabo en el bosque templado de la comunidad de Calpulálpam de Méndez del municipio del mismo nombre (17°18´21" N y 96°26´42" O), dentro de la región de la Sierra Juárez en el estado de Oaxaca (Uzachi, 2003). La altitud varía de 2000 m a 3080 m snm (Ríos-Altamirano et al, 2016). El clima según la clasificación de Köppen, modificado por García (1988), corresponde a C (w2)(w): templado subhúmedo, con régimen de lluvias en verano.…”
Section: áRea De Estudiounclassified
“…En la región de la Sierra Juárez en el estado de Oaxaca, a partir de la década del año 2000 ha sido cada vez más frecuente que se realicen estudios sobre el manejo forestal y sus efectos en la estructura, composición y diversidad en el bosque mixto (p. ej. Castellanos et al, 2008;Ríos-Altamirano et al, 2016). Sin embargo, a excepción de Hernández (2007), ninguno de estos estudios utilizó la medición de sitios permanentes como una fuente de información; por lo que estudios sobre la dinámica y la demografía de rodales han sido escasos.…”
Section: Introductionunclassified